Deepwater Horizon: The Importance of Public Relations as an Indicator of Corporate Sustainability - Riran Aulia Windari; Theresia Angelina; Nayla Amalia Fitri; Hardi Alunaza; Yusawinur Barella (PT Syamilah Literasi Islami, 2024)
The explosion on the British Petroleum (BP) oil drilling rig, Deepwater Horizon, in the Gulf of Mexico on April 20, 2010 attracted global attention as one of the worst environmental disasters in history. This research aims to analyze the events that occurred and conclude the relationship between the community and the British Petroleum Company after the explosion. The findings show that BP’s management failures and inadequate response to this disaster led to a significant decline in the company’s reputation and a major financial impact. By applying a qualitative approach, this journal collects secondary data from various relevant sources. Data and information were obtained through internet-based research techniques from reliable sources. The results of this research provide an overview of the importance of effective crisis management and appropriate communication in dealing with critical situations, as well as the long-term impact on the company’s image and reputation.